Method of making a heterogeneous lap joint between a nickel-coated steel sheet and a multilayer copper foil

CN122956102APending Publication Date: 2026-10-23E ONE MOLI ENERGY CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610359859.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-17
Filing Date
2026-03-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,尽管蓝光激光在铜焊接方面展现出巨大的潜力,但目前市售的蓝光激光技术仍存在一些限制,阻碍了其在量产制造镀镍钢片与多层铜箔等异质材料搭接焊点上的广泛应用

Benefits of technology

[0021]与现有技术不同,根据本发明的方法采用高功率绿光激光焊接,并无采用蓝光激光焊接的缺点,且能高效率、高品质地制造镀镍钢片与多层铜箔的异质搭接焊点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122956102A_ABST
    Figure CN122956102A_ABST
Patent Text Reader

Abstract

A method for manufacturing a heterogeneous lap joint of a nickel-plated steel sheet and N layers of copper foil, wherein N is a natural number, includes the steps of: pressing the nickel-plated steel sheet against the N layers of copper foil; and focusing a high-power green laser beam on a surface of the nickel-plated steel sheet according to the method of the present application, so that the high-power green laser beam melts through the nickel-plated steel sheet and the N layers of copper foil, and then solidifies to form the heterogeneous lap joint of the nickel-plated steel sheet and the N layers of copper foil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing heterogeneous lap joints of nickel-plated steel sheets and multilayer copper foils, and more particularly to a method for manufacturing heterogeneous lap joints of nickel-plated steel sheets and multilayer copper foils using lasers with high efficiency and high quality. Background Technology

[0002] Lithium-ion batteries, with their superior characteristics such as high energy density, long cycle life, and low self-discharge rate, have become indispensable key components in electric vehicles, power tools, drones, and even energy storage systems. Their core operation relies on the back-and-forth insertion and extraction of lithium ions between the positive and negative electrodes to achieve the storage and release of electrical energy.

[0003] In lithium-ion battery structures, the cathode material plays the role of providing lithium ions. Common materials include lithium cobalt oxide (LiCoO2, the early mainstream material with high energy density but high cost), lithium manganese oxide (LiMn2O4, with lower cost but cycle life and high-temperature performance need improvement), lithium nickel oxide (LiNiO2 and its modified materials, such as NCM and NCA, with high energy density as a development trend), and lithium iron phosphate (LiFePO4, with high safety and long cycle life but relatively low energy density). To effectively collect and conduct current, aluminum foil is usually used as the current collection layer of the cathode.

[0004] The primary function of the anode material is to store lithium ions that have moved from the cathode, and its lithium storage capacity directly determines the battery's energy density. Currently, graphite-based materials are widely used as anode materials due to their low cost and stable performance. To further improve energy density, researchers are actively developing and applying novel anode materials such as silicon and graphene, which theoretically have higher lithium storage capacities. Similar to the cathode, the anode also requires a current collection layer, typically made of copper foil, which has excellent conductivity and high chemical stability.

[0005] The charging and discharging process of a lithium battery is a process of lithium-ion migration. During charging, an external power source drives lithium ions to escape from the positive electrode, move through the electrolyte to the negative electrode, and embed themselves in the layered structure or micropores of the negative electrode material. The more lithium ions embedded, the higher the battery's charging capacity. During discharging, the lithium ions in the negative electrode material are released, return to the positive electrode through the electrolyte, and eventually collect at the aluminum current collecting layer of the positive electrode, forming an output current.

[0006] For cylindrical lithium-ion batteries, to ensure safety and reliability, they are typically sealed with a cylindrical nickel-plated steel can made of nickel-plated steel sheets. This nickel-plated steel can not only provide physical protection but, more importantly, serves as the grounding terminal for the negative electrode. To form a complete current path, the copper current-collecting layer at the bottom of the battery, composed of multiple layers of copper foil, must have a reliable electrical connection with this nickel-plated steel can.

[0007] Currently, resistance welding technology is commonly used in the mass production of these cylindrical lithium batteries to connect the bottom of the nickel-plated steel can to the copper foil inside the battery. However, this welding method has revealed some significant drawbacks in actual production. For example, it is prone to solder spatter, leading to a decrease in yield; open solder joints can cause poor electrical connections, resulting in excessively high contact resistance, which affects battery performance and safety; poor contact at the joint can also lead to increased internal resistance of the battery, affecting charging and discharging efficiency.

[0008] Faced with the urgent future demand for higher energy density lithium-ion batteries, existing resistance welding technology has become a bottleneck in improving lithium-ion battery performance and production efficiency. Therefore, there is an urgent need to develop and implement more advanced and reliable connection technologies to overcome the shortcomings of resistance welding and ensure that the quality and performance of next-generation lithium-ion batteries reach higher standards. This will help promote the further development of electric transportation and energy storage technologies.

[0009] Laser welding, as an advanced material joining technology, relies on a high-power-density laser beam as its energy source to precisely melt materials and form a strong weld joint. Compared to traditional low-to-medium energy-density welding methods, laser welding boasts a high power density of up to 10... 6 W / cm 2 Laser welding, with its high energy density, exhibits numerous superior advantages, including extremely low total heat input. This significantly reduces the heat-affected zone of the base material, thereby minimizing deformation caused by thermal stress. Furthermore, laser welding can achieve high-quality welds with high aspect ratios (weld depth to width), which is crucial for applications requiring high strength and sealing. More importantly, laser welding also offers advantages such as high welding speed, precise control, and ease of automation, making it highly favored in modern industrial production.

[0010] However, different metallic materials exhibit significant differences in their energy absorption rates to laser beams of different wavelengths. This absorption rate directly determines the efficient utilization of energy during the welding process, thus greatly affecting the quality of the weld. A high absorption rate means that more laser energy is absorbed by the material and converted into heat energy, achieving more efficient melting and welding. Therefore, selecting a laser source wavelength that matches the specific properties of different metals, such as their physical and chemical properties, is crucial. Please refer to... Figure 1 , Figure 1 The data shown are the absorption rates of five common metals (copper, gold, nickel, iron, and aluminum) at different laser wavelengths.

[0011] from Figure 1As can be clearly seen, copper metal has a very low absorption rate for traditional yttrium aluminum garnet (YAG) lasers with a wavelength of 1064 nm, only about 2%. This means that if a laser beam of this wavelength is used for welding copper metal, most of the laser energy will not be effectively absorbed by the copper surface, and instead, strong reflection or scattering will occur. This low absorption rate not only makes it difficult to form a stable and reliable weld joint, but more seriously, the reflected or scattered laser beam may damage the optical components in the laser system, such as the laser lens and cavity, making copper welding using traditional YAG lasers very difficult or even infeasible.

[0012] In contrast, when using a shorter wavelength 450 nm blue laser for welding, the absorption rate of blue light on the copper surface can be significantly increased to 43%. This substantial improvement makes blue laser welding of copper possible and has spurred numerous research publications on the subject. However, despite the enormous potential of blue lasers in copper welding, currently available blue laser technology still faces some limitations, hindering its widespread application in mass production of weld joints between dissimilar materials such as nickel-plated steel sheets and multilayer copper foils. These limitations mainly include: the need to improve long-term stability, especially under high-power continuous operation; the relatively large laser spot size, which may affect welding precision and fine structures; insufficient output power to meet the demands of large-scale production; and a lack of mature and reliable mass-production-grade scanning mirror assemblies and other peripheral equipment. These technical bottlenecks urgently need to be overcome to truly apply blue lasers to the high-efficiency, high-quality welding production of lithium-ion battery components. Summary of the Invention

[0013] Therefore, the technical problem to be solved by the present invention is to provide a method for manufacturing heterogeneous lap joints of nickel-plated steel sheets and multilayer copper foils using lasers with high efficiency and high quality.

[0014] According to a preferred embodiment of the present invention, a method for manufacturing a heterogeneous lap joint between a nickel-plated steel sheet and N layers of copper foil involves first pressing the nickel-plated steel sheet against N layers of copper foil, where N is a natural number. Finally, according to the preferred embodiment of the present invention, a high-power green laser beam is focused onto the surface of the nickel-plated steel sheet, causing the high-power green laser beam to melt through the nickel-plated steel sheet and the N layers of copper foil, and then solidify to form a heterogeneous lap joint between the nickel-plated steel sheet and the N layers of copper foil.

[0015] In one specific embodiment, the power range of the high-power green laser beam can be from 200W to 1000W.

[0016] In one specific embodiment, the wavelength range of the high-power green laser beam can be from 500nm to 550nm.

[0017] In one specific embodiment, the first thickness of the nickel plating layer on the nickel-plated steel sheet can range from 1 μm to 5 μm.

[0018] In one specific embodiment, the second thickness of the nickel-plated steel sheet can range from 200 μm to 600 μm.

[0019] In one specific embodiment, the third thickness of each copper foil layer can range from 5 μm to 20 μm.

[0020] In one specific embodiment, the number of N copper foil layers can range from 1 to 30.

[0021] Unlike existing technologies, the method according to the present invention uses high-power green laser welding, which avoids the disadvantages of using blue laser welding, and can efficiently and effectively manufacture heterogeneous lap joints between nickel-plated steel sheets and multilayer copper foils.

[0022] The advantages and spirit of the present invention can be further understood through the following detailed description of the invention and the accompanying drawings. Attached Figure Description

[0023] Figure 1 This is a graph showing the absorption rate of five common metals (copper, gold, nickel, iron, and aluminum) at different laser wavelengths.

[0024] Figure 2 , Figure 3 and Figure 4 These are side view schematic diagrams of the structures obtained at different steps in the method for manufacturing heterogeneous lap joints of nickel-plated steel sheets and N layers of copper foil according to a preferred embodiment of the present invention.

[0025] Explanation of icon numbers:

[0026] 1: Nickel-plated steel sheet

[0027] 10: Steel sheet

[0028] 102: Upper surface

[0029] 104: Lower surface

[0030] 12: Nickel plating layer

[0031] 2: Copper foil

[0032] 3: High-power green laser beam

[0033] 4: Melting Zone

[0034] 5: Heterogeneous lap joint Detailed Implementation

[0035] Please see Figure 2 , Figure 3 and Figure 4 These figures are schematic side views illustrating the structures obtained at different stages of the method for manufacturing a heterogeneous lap joint 5 of a nickel-plated steel sheet 1 and an N-layer copper foil 2 according to a preferred embodiment of the present invention, where N is a natural number.

[0036] like Figure 2 As shown, the nickel-plated steel sheet 1 comprises a steel sheet 10 and a nickel plating layer 12. The steel sheet 10 has an upper surface 102 and a lower surface 104. The nickel plating layer 12 covers the upper surface 102 and the lower surface 104 of the steel sheet 10, respectively.

[0037] In one specific embodiment, the first thickness of the nickel plating layer on the nickel-plated steel sheet can range from 1 μm to 5 μm.

[0038] In one specific embodiment, the second thickness of the nickel-plated steel sheet can range from 200 μm to 600 μm.

[0039] Similarly, Figure 2 As shown, according to a preferred embodiment of the present invention, a method for manufacturing a heterogeneous lap joint 5 between a nickel-plated steel sheet 1 and an N-layer copper foil 2 firstly involves pressing the nickel-plated steel sheet 1 against the N-layer copper foil 2. Figure 2 In the process, the nickel-plated steel sheet 1 is pressed against the uppermost copper foil 2 of the N layers of copper foil 2 by the nickel-plated layer 12 covering the lower surface 104 of the steel sheet 10.

[0040] In one specific embodiment, the third thickness of each copper foil layer can range from 5 μm to 20 μm.

[0041] In one specific embodiment, the number of N copper foil layers can range from 1 to 30.

[0042] Finally, as Figure 3 As shown, the method according to a preferred embodiment of the present invention involves focusing a high-power green laser beam 3 onto the surface of a nickel-plated steel sheet 1, causing the high-power green laser beam 3 to melt through the nickel-plated steel sheet 1 and the N-layer copper foil 2 to form a molten zone 4. After the molten zone 4 solidifies, it forms a heterogeneous lap joint 5 between the nickel-plated steel sheet 1 and the N-layer copper foil 2. Figure 4 As shown. At Figure 3 In the process, a high-power green laser beam 3 is focused onto the nickel-plated layer 12 covering the upper surface 102 of the steel sheet 10. In practice, multiple independent heterogeneous lap joints 5 must be formed between the nickel-plated steel sheet 1 and the N-layer copper foil 2. Figure 4 In the diagram, only one heterogeneous lap joint 5 is shown as a representative example.

[0043] In one specific embodiment, the power range of the high-power green laser beam 3 can be from 200W to 1000W.

[0044] In one specific embodiment, the wavelength range of the high-power green laser beam 3 can be from 500nm to 550nm.

[0045] Several embodiments of the present invention use a high-power green laser beam 3 to perform heterogeneous welding of a nickel-plated steel sheet 1 and a multilayer copper foil 2. The nickel-plated steel sheet 1 has a length of 55 mm, a width of 40 mm, and a thickness of 300 μm. Both the upper surface 102 and the lower surface 104 of the steel sheet 10 are plated with 2 μm thick pure nickel to form a nickel plating layer 12. Each copper foil 2 is selected with a length of 55 mm, a width of 40 mm, and a thickness of 8 μm. Twenty copper foils 2 of the same thickness are stacked to form a multilayer copper foil 2. The nickel-plated steel sheet 1 and the multilayer copper foil 2 are then stacked and fixed in a fixture and pressed tightly. A TruDisk 2021 green laser manufactured by TRUMPF is used. This laser has a maximum output power of 2000 W, a beam wavelength of 515 nm, and a spot diameter of 255 μm. The welding process employs a rectangular pulse wave mode. A high-power green laser beam 3 emits a 20ms laser pulse every 0.5 mm. After each 20ms laser pulse, the molten zone 4 formed between the nickel-plated steel sheet 1 and the multilayer copper foil 2 solidifies, forming a heterogeneous lap weld 5. In practice, multiple independent heterogeneous lap welds 5 must be formed on the nickel-plated steel sheet 1 and the multilayer copper foil 2. The high-power green laser beam 3 first irradiates and focuses on the surface of the nickel-plated steel sheet 1, melting through it and then continuing to melt the multilayer copper foil 2. When the high-power green laser beam 3 stops irradiating, the molten zone solidifies, forming the heterogeneous lap weld 5, as illustrated in the diagram below. Figure 4 As shown.

[0046] In Embodiment 1 of the present invention, high-purity nitrogen gas is blown onto the surface of the nickel-plated steel sheet 1 during welding to prevent oxidation of the weld joint. The nitrogen flow rate is 40 L / min. When the laser power is 240 W, the nickel-plated steel sheet 1 is not melted through. When the laser power is increased to 260 W, the nickel-plated steel sheet 1 is melted through, but the multilayer copper foil 2 is not melted at all, so no heterogeneous lap weld joint 5 is formed. When the laser power is increased to 280 W, the nickel-plated steel sheet 1 is melted through and the first layer of copper foil 2 of the multilayer copper foil 2 is also melted, so the heterogeneous lap weld joint 5 is successfully formed.

[0047] In Embodiment 2 of the present invention, high-purity nitrogen gas is blown onto the surface of the nickel-plated steel sheet 1 during welding to prevent oxidation of the weld joint; the nitrogen flow rate is 40 L / min. When the laser power is 300 W, the nickel-plated steel sheet 1 is melted through and the first six layers of the multilayer copper foil 2 are also melted, thus successfully forming a heterogeneous lap weld joint 5; when the laser power is 340 W, the nickel-plated steel sheet 1 is melted through and the first ten layers of the multilayer copper foil 2 are also melted, thus successfully forming a heterogeneous lap weld joint 5; when the laser power is 380 W, the nickel-plated steel sheet 1 is melted through and all 20 layers of the multilayer copper foil 2 are melted, thus successfully forming a heterogeneous lap weld joint 5.

[0048] In Embodiment 3 of the present invention, high-purity nitrogen gas was not blown onto the surface of the nickel-plated steel sheet 1 for protection during welding. When the laser power was 360 W, the nickel-plated steel sheet 1 was melted through and all 20 layers of copper foil 2 in the multilayer copper foil 2 were melted, thus successfully forming a heterogeneous lap joint 5.

[0049] Through the detailed description of the present invention above, it can be clearly understood that the method according to the present invention uses high-power green laser welding, which is different from blue laser welding and does not have the disadvantages of blue laser welding. Moreover, it can efficiently and with high quality manufacture heterogeneous lap joints of nickel-plated steel sheets and multilayer copper foils.

[0050] The detailed description of the preferred embodiments above is intended to more clearly illustrate the features and spirit of the present invention, and is not intended to limit the scope of the invention to the preferred embodiments disclosed above. Rather, the aim is to cover various modifications and equivalent arrangements within the scope of the claims to which this invention is sought. Therefore, the scope of the claims to which this invention is sought should be interpreted in the broadest possible sense based on the foregoing description, so as to cover all possible modifications and equivalent arrangements.

Claims

1. A method for manufacturing a heterogeneous lap joint between a nickel-plated steel sheet and N layers of copper foil, where N is a natural number, the method comprising the following steps: The nickel-plated steel sheet is pressed against the N-layer copper foil; and A high-power green laser beam is focused onto the surface of the nickel-plated steel sheet, causing the high-power green laser beam to melt through the nickel-plated steel sheet and the N layers of copper foil, and then solidify to form the heterogeneous lap joint of the nickel-plated steel sheet and the N layers of copper foil.

2. The method according to claim 1, wherein the power range of the high-power green laser beam is from 200W to 1000W.

3. The method according to claim 2, wherein the wavelength range of the high-power green laser beam is from 500 nm to 550 nm.

4. The method according to claim 3, wherein the first thickness of the nickel plating layer of the nickel-plated steel sheet ranges from 1 μm to 5 μm.

5. The method of claim 3, wherein the second thickness of the nickel-plated steel sheet ranges from 200 μm to 600 μm.

6. The method of claim 3, wherein the third thickness of each copper foil layer ranges from 5 μm to 20 μm.

7. The method of claim 3, wherein the number of N copper foil layers ranges from 1 to 30.